2014
DOI: 10.1590/s0102-05362014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Características dos substratos na absorção de nutrientes e na produção de gérbera de vaso

Abstract: O sistema de produção em substratos vem sendo empregado na maioria dos cultivos comerciais de plantas ornamentais, dentre elas a gérbera. De acordo com Guerrero et al. (2012), nos últimos anos o cultivo comercial de gérbera de vaso e de corte tornou-se de grande importância econômica para a floricultura. Porém, sua introdução como flor envasada é recente no Brasil e ainda são necessários muitos estudos, especialmente aqueles relacionados com a determinação das propriedades físicas e químicas dos substratos, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
2
9
0
9
Order By: Relevance
“…The acidification of the substrates may have occurred due to the plant growth and electrogenic pump activity, H + -ATPase (YI-YONG et al, 2011). These results are in conformity with Ludwig et al (2014), who also observed a decrease in pH of pine bark substrate that turned semi-decomposed at the end of the cultivation cycle of Gerbera jamesonii. It is also noteworthy here that the changes in the substrates pH can occur even without cultivated plants on it, but only with the water addition to the medium.…”
Section: Experiments IIsupporting
confidence: 92%
See 1 more Smart Citation
“…The acidification of the substrates may have occurred due to the plant growth and electrogenic pump activity, H + -ATPase (YI-YONG et al, 2011). These results are in conformity with Ludwig et al (2014), who also observed a decrease in pH of pine bark substrate that turned semi-decomposed at the end of the cultivation cycle of Gerbera jamesonii. It is also noteworthy here that the changes in the substrates pH can occur even without cultivated plants on it, but only with the water addition to the medium.…”
Section: Experiments IIsupporting
confidence: 92%
“…Among chemical properties of the material or mix (substrate), pH and electrical conductivity (EC) holds great importance (KÄMPF et al, 2006;LUDWIG et al, 2014). Constant monitoring of these properties provides the growers an overview of the salinization and acidification of the growth medium, thus making it possible to fertilize substrates without damaging of the growth of the seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the results of this experiment, there were an average of two flowers per pot, therefore, class II. Ludwig et al (2010) analyzed two gerbera cultivars (Red and Cherry) grown in different substrates, and found that the Red cultivar was characterized by being more floriferous when compared to Cherry, which had fewer inflorescences, however larger. The authors found a propensity towards a better acceptance by plants consisted of inflorescences with a larger diameter, even if their number is lower.…”
Section: Resultsmentioning
confidence: 99%
“…O sistema de produção em substratos vem sendo empregado na maioria dos cultivos comerciais de plantas ornamentais (LUDWIG et al, 2014), e em função dos recipientes apresentarem um volume reduzido para o crescimento radicular, deve-se atentar para a questão nutricional. Para evitar perdas de qualidade, é importante realizar o manejo nutricional, sendo a condutividade elétrica da solução do substrato uma medida indireta de nutrientes disponíveis para as plantas (MOTA et al, 2016;TORRES et al, 2010), que pode ser efetuada de forma rápida no próprio ambiente de cultivo.…”
Section: Introductionunclassified